Cellulase production using a combination of carrot peel and corn husk (tusa) residues under solid-state fermentation - Mora Villalobos, Vanny Emileth (2024)
Agricultural wastes are characterized by bioactive compounds that can be used to produce different byproducts, including enzymes, which are obtained through solid state fermentation (SSF). The goal of this study was to evaluate the initial pH and moisture conditions of a substrate composed of carrot peels and corn husk residues (tusa) by SSF to obtain cellulase enzymes. Carrot and corn wastes were characterized to determine their physicochemical properties, confirming their suitability for the fermentation process. It was found that endoglucanase enzyme activity increased with time and was favored at a humidity of 75% and a pH of 5.2, reaching values above 300 U/mg protein. However, no significant trends were observed in exocellulase activity related to the study´s factors. Although the use of agro-industrial wastes to obtain high-value molecules has been widely studied, combining carrot and corn wastes as a substrate for cellulase production using Cladosporium sp. _V3 (GenBank No. PP931187) isolated from pineapple wastes has been poorly characterized.